Ethnicity, Commodity, In/Corporation - Meiu, George Paul (Book collections on Project MUSE.)
In the economics of everyday life, even ethnicity has become a potential resource to be tapped, generating new sources of profit and power, new ways of being social, and new visions of the future. Throughout Africa, ethnic corporations have been repurposed to do business in mining or tourism; in the USA, Native American groupings have expanded their involvement in gaming, design, and other industries; and all over the world, the commodification of culture has sown itself deeply into the domains of everything from medicine to fashion. Ethnic groups increasingly seek empowerment by formally incorporating themselves, by deploying their sovereign status for material ends, and by copyrighting their cultural practices as intellectual property. Building on ethnographic case studies from Kenya, Nepal, Peru, Russia, and many other countries, this collection poses the question: Does the turn to the incorporation and commodification of ethnicity really herald a new historical moment in the global politics of identity?